Sistem Pakar untuk Mendiagnosa Penyakit pada bebek Berbasis Android - Setiawan, Muhammad Galih; , Fatah Yasin Al Irsyadi, S.T., M.T (2016)
Duck is kind of animals poultry communities that usually breeded by people such as meat or egg. The amount of this population make it easier to infected of the disease. A lot of people do not understand about the duck diseases caused by bacteria, virus, fungi and parasite. Expert system is an used to handle the duck diseases. It created to diagnose the duck diseases caused by bacteria, virus, fungi and parasite. This expert system not only give information about duck diseases and indications but also give information about how to treat it. The method of this expert system is forward chaining method. The result of this test system show that the system can determine the duck diseases and the treatment, based on the indication that was selected by user.